Analysis of Gender Equality in Indonesia,Egypt and Jordan - Harris, Anestya Riskina (2006)
The issue of gender equality is something un-new in the world today. Long has the world watch and analyze the differences in many live aspects based on sexual differentiation and long have experts and scholars from all over the world despite of religion, nationality and sex group has tried to search and analyze the causes and the remedies of it. However, it is assumed that Muslim world share one world that far different from the West and that Muslim anywhere in the world is the same simply because they share same religion. In this paper writer try to analyze the effects of certain important variables such as religion and culture on gender equality to find the differences or similarities in the level of gender equality and the causes of it in these three countries. Further analyzes are developed through country analyzes to find the real condition of gender equality in each country. And the findings are that historical, political and geographic condition of Indonesia has allow Indonesian female to feel more equal with Indonesian male while analyzes on Egypt and Jordan shows that Egyptian and Jordanian female are suffering from large gap between female and male caused by the powerful ruling regime in the region thus gender equality in Indonesia, Egypt and Jordan are in different level despite their similarities as Muslim countries and despite the fact that Indonesia was once being largely influenced by Muslims coming from Middle Eastern countries in its early days.